Knowledge, attitude and practice towards insomnia and sleep hygiene among patients with chronic insomnia in Northwest China in 2023: a cross-sectional survey - Jing Zhu; Xin Li; Jinghua Wang; Shiping Zhang; Zhibo Zhu; Tao Kang; Yikang Zhao; Lijuan Zhu (BMJ Open)
Objectives To investigate the knowledge, attitude and practice (KAP) towards insomnia and sleep hygiene among patients with chronic insomnia.Design Web-based cross-sectional survey.Setting Shaanxi Provincial People’s Hospital (northwest China) between January 2023 and May 2023.Participants Patients with chronic insomnia.Primary and secondary outcome measures Demographic characteristics and KAP towards insomnia and sleep hygiene were collected by distributing a questionnaire developed by the authors.Results A total of 613 people participated in this study, with a Mean Knowledge Score of 7.63±2.56 (total score of 12), a Mean Attitude Score of 48.39±6.643 (total score of 70) and a Mean Practice Score of 42.37±8.592 (total score of 70). Knowledge was significantly correlated with attitude (r=0.447, p<0.001) and practice (r=0.327, p<0.001), and attitude was significantly correlated with practice (r=0.486, p<0.001). Multivariable logistic regression showed that higher knowledge (OR=1.181 (1.062–1.314), p=0.002) and better attitude (OR=1.171 (1.124–1.221), p<0.001) were independently associated with good practice. According to the structural equation modelling analysis, knowledge directly influenced practice (β=0.457, p=<0.001) and attitude (β=1.160, p=<0.001), while attitude influenced practice (β=0.550, p=<0.001).Conclusion The KAP towards insomnia and sleep hygiene among patients with chronic insomnia in Northwest China in 2023 was moderate, with better practice showing signs of being influenced by better knowledge and more positive attitudes.